The Role of the Principal in Improving the Quality of Education - Ruhen; Romiftahul Ulum (Journal of Practice Learning and Educational Development, 2025)
This study aims to describe the role of the principal in improving the quality of education at SMA Nurul Iman, Kokop District, Bangkalan Regency, with a focus on his role as a leader and supervisor. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through interviews, observations, and documentation of the principal, teachers, staff, and students. The results of the study indicate that the principal of SMA Nurul Iman has actively carried out his role as a leader by providing guidance to educators in the use of interesting and relevant learning models. The principal also encourages teacher professional development through training and facilitation of learning facilities. In addition, supervision is carried out routinely as an effort to supervise and foster the implementation of learning. The conclusion of this study is that the principal has a strategic role in improving the quality of education through effective leadership, strengthening collaboration, and implementing continuous supervision functions. These findings reinforce the importance of the role of the principal as the main driver in creating a quality educational environment.